ANALISIS KONDISI EKSISTING STADION TELADAN TERHADAP STANDAR FIFA - Nasution, Anisyah Khairani; Fitri, Rahmadhani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
A stadium is a building used to hold football events or events in which there is a field or stage surrounded by seats and stands for spectators. In Indonesia, there are only three proper stadiums for national and international events. The rest is only for local matches. For the sake of advancing the level of a team, a stadium that has FIFA standards is very important and will also be the pride of the team. A feasibility analysis was carried out to determine the feasibility of an exemplary stadium by using a questionnaire. The purpose of this research is to conduct a stadium feasibility study in accordance with FIFA standards. The results of this study indicate that conditions in model stadiums do not meet FIFA standards. Analysis of the Existing Conditions of Exemplary Stadiums Against FIFA Standards, intended for football clubs and events, football lovers and all residents of Medan City to carry out football matches and exercise for residents by providing the main facilities of Football Stadiums for playing and watching matches.